A bibliometric analysis of autophagy in lung diseases from 2012 to 2021 - Lin, Feihong; Chen, Yong; Mo, Wei; Zhou, Huanping; Xiao, Zhuoran; Hu, Song; Shi, Xuan; Liu, Meiyun; Wei, Juan; Zhu, Wanli; Wang, Sheng; Lv, Xin (Frontiers in Immunology, 2022)
Background Autophagy refers to the process in which cells wrap their damaged organelles or unwanted proteins into a double-membrane structure and direct them to lysosomes for degradation. Autophagy can regulate many lung diseases such as pulmonary hypertension, acute lung injury, and lung cancer. However, few bibliometric studies on autophagy are available. The aim of the present study was to clarify the role of autophagy in lung diseases by bibliometric analysis. Methods Publications were retrieved from the 2012–2021 Science Citation Index Expanded of Web of Science Core Collection on 20 September 2022. Bibliometrix package in R software was used for data retrieval. VOSviewer and CiteSpace were used to visualize the research focus and trend regarding the effect of autophagy on lung disease. Results A total of 4,522 original articles and reviews on autophagy in lung diseases published between 2012 and 2021 were identified. China had the largest number of published papers and citations, whereas the United States (US) ranked first in the H-index and G-index. Moreover, cooperation network analysis showed close cooperation between the US, China, and some European countries, and the top 10 affiliates were all from these countries and regions. Bibliometric analysis showed that “autophagy” and “apoptosis” were the keywords with the highest frequency. During the past decade, most studies were concerned with basic research on pathways related to the regulatory role of autophagy in the inhibition and attenuation of lung diseases. Conclusion The study of autophagy in lung diseases is still in the development stage. The information published in these articles has helped researchers understand further the hot spots and development trends in the field more and learn about the collaboration network information regarding authors, countries, and institutions, as well as the paper citation correlation. More studies have been performed to gain deeper insights into the pathogenesis of autophagy by focusing on the links and effects between various diseases. More recently, research in this field has paid increasing attention to the function of autophagy in COVID-19–related lung diseases.